Protection of Migrants' Rights in Serbia: From Humanitarian Protection to Integration and Social Inclusion - Ćopić, Sanja; Ćopić, Slobodan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
Ministry of Interior of the Republic of Serbia, Border Police Directorate Serbia faced the increase in irregular migration, particularly during 2015, when it found itself in the so-called Western Balkan migration route. The state, with the assistance of international organizations and local civil society organizations, has taken a number of measures to provide migrants and refugees with humanitarian assistance, including accommodation, health care, assistance and support, and access to the asylum procedure. The lessons learnt have served to make certain improvements in practice, as well as a basis for further reforms of the normative framework relevant for the asylum system and migration policy. This paper aims to illustrate the extent to which the institutions' responses to the protection of the rights of migrants are in line with international standards, which challenges institutions in Serbia face, and what direction for further work on ensuring integration and social inclusion of refugees. The article is based on triangulation of data collected by qualitative analysis of the international and national legal framework relevant for the protection of the rights of refugees and migrants and analytical documents of state institutions, independent agencies and civil society organizations on the level of respect of the rights of refugees and migrants in Serbia. The paper starts with a brief overview of international standards for the protection of migrants' rights. This is followed by the review of some measures and activities of institutions aimed at humanitarian care of migrants in Serbia, on the one hand, and their integration and social inclusion, on the other, and the analysis of the normative framework in the field of asylum. The concluding part brings some challenges faced by the institutions and possible steps for more adequate and efficient integration and social inclusion of refugees and migrants.